The neuropathological contribution of prenatal inflammation to schizophrenia. (January 2011) - Meyer, Urs; Weiner, Ina; McAlonan, Grainne M; Feldon, Joram
Evaluation of: Ellman LM, Deicken RF, Vinogradov S et al. Structural brain alterations in schizophrenia following fetal exposure to the inflammatory cytokine interleukin-8. Schizophr. Res. 121, 46–54 (2010). Maternal infection and/or inflammation during pregnancy has been repeatedly shown to elevate the risk of schizophrenia and related psychotic disorders in offspring. However, the relative contribution of such immune-related prenatal insults to specific neuropathological outcomes in schizophrenia remains essentially unknown. The study by Ellman et al. is the first to explore whether prenatal levels of the proinflammatory cytokine, IL-8, are associated with the volume of specific brain regions in patients diagnosed with schizophrenia spectrum disorder. The authors provide new data to support a significant association between higher prenatal IL-8 levels in the second/third trimester of pregnancy and greater ventricular cerebrospinal fluid volume in adult schizophrenia spectrum cases. In addition, the results provide evidence for a significant relationship between higher prenatal IL-8 levels and lower volumes in the left entorhinal cortex and right posterior cingulate. The findings provided by Ellman et al., together with the results obtained in other epidemiological studies and experimental animal research, should encourage basic researchers and clinicians alike to make efforts towards the investigation of maternal immunomodulatory interventions that may help alleviate abnormal brain development and long-term psychotic illness in offspring.